Predicting Career Paths: An Exploration of the Determinants of Career Choice of Women in Nursing, Banking and Teaching Professions in Nigeria Using Logistic Regression - Essien, Blessing Stephen; Umoh, Mfon Gabriel (NIU Journal of Social Sciences, 2025)
Women are a significant sociological group whose behaviours, motivations and values are sometimes incomprehensible in many contexts including workplace setting.  This study examines the factors influencing career choices among women in nursing, banking and teaching professions in Uyo Local Government Area of Akwa Ibom State, Nigeria. The research considers parental influence, financial benefits, job security, leisure time, and personal interest as key determinants of career choice. A descriptive research design was employed, with a sample size of 329 participants selected from a population of 2,310. Questionnaires were used to collect data, which were analysed using frequency tables, simple percentages, and logistic regression. The findings reveal that parents significantly influence their daughter’s career paths through counseling, role modeling, and financial support. Financial benefits were a major consideration for women in banking, with most expressing satisfaction with their current financial incentives. Job security was found to be higher in teaching and nursing compared to banking. The study recommends that parents foster open discussion, encouraging daughters to pursue careers based on their personal aspirations rather than parental expectations. Employers in nursing and teaching professions should enhance financial benefits to prevent women from gravitating towards banking. Additionally, organizations should implement flexible working arrangements to support women’s career advancement and work-life balance. Keywords: Career Choice, Determinants, Women, Comparison, Nigeria.